Predictors of favorable outcome and mortality after endovascular thrombectomy in young Chinese patients with large vascular occlusions - Li, Zhiqiang; Wu, Shuhui; Liang, Fang; Tan, Fengjiao; Li, Ning; Bao, Mengxin (Frontiers in Neurology, 2023)
Background Endovascular thrombectomy (EVT) has evolved into the standard treatment for patients with acute ischemic stroke (AIS) and large vessel occlusion (LVO). However, little information is available on the management of EVT in young patients with AIS-LVO in China. The purpose of this study was to assess the favorable outcomes and mortality rates after 90 days of EVT in young Chinese patients with AIS-LVO and their predictors. Methods This retrospective study included young Chinese patients aged 18–50 years with AIS-LVO. The primary efficacy endpoint was the modified Rankin scale (mRS) score at day 90, and the primary safety endpoint was mortality within 90 days. Using univariate and multivariate logistic regression analyses, the associations between clinical, imaging, and procedure variables and favorable (mRS 0–2) outcomes or mortality at 90 days were analyzed. Results A total of 113 patients were included in the study with a mean age of 43.1 ± 6.3 years. Symptomatic intracranial hemorrhage (sICH) occurred in 8 (7.1%) patients. Favorable functional outcomes (mRS 0–2) were recovered in 42.5% of patients at 3 months. After 90 days, the mortality rate was 32.3%. Multivariate analysis revealed that the increase in admission NIHSS score was associated with a lower probability of functional independence (aOR 1.08, 95% CI 1.02–1.15, p = 0.01 and aOR 1.01, 95% CI 1–1.01, p = 0.008, respectively) and a higher probability of death at 90 days (aOR 1.1, 95% CI 1.03–1.18, p = 0.007 and aOR 1.00, 95% CI 1–1.01, p = 0.021, respectively). Conclusion This study demonstrate that EVT provides higher rates of arterial recanalization, rather than better favorable outcomes and lower risk of death at 3 months in young Chinese patients with AIS-LVO. Increased NIHSS scores on admission may be associated with poor patient prognosis.